THE Epidemiology of Cancers in Department of Oncology at University Hospital Antanambao Toliara, Madagascar - Randriamalala, Ruffin; Tika, Lovasoa; Harivony, Tovo; Randrianjaka, Hery; Margueritte, Vonimiarantsoa; Rakotoniaina, Andriamiarimbola Irène; Riel, Andry Mampionona; Rafaramino, Florine (International Journal For Research In Applied And Natural Science, 2019)
Introduction: In August 2016, the Antanambao Toliara University department of Oncology and Multidisciplinary Medicine was created. This is the first oncology department in the South West region of Madagascar. Our objective was to determine the number of cancer cases recorded in this department as well as their socio-demographic, clinical and therapeutic characteristics. Methods : It was a retrospective descriptive study over 15 months from October 1st, 2016 to December 31st, 2017. Patients with cytologic or histological proof of theirs cancers were included. Results : We have collected 50 cases of cancers. The age of patients ranged from 10 to 80 years with an average age of 49.5 years. Women accounted for 82% of patients. The Vezo ethnic group predominated with 18 patients (36%). Forty percent of patients came from the urban district of Toliara. Gynecological cancers were the most common (66%), including cervix (28%) and breast (26%) cancers, followed by cancers of the head and neck (16%). Patients were initially diagnosed at the locally advanced (70%) and metastatic (22%) stages. They were treated by surgery alone (46%), chemotherapy alone or combined (44%) and radiotherapy (4%). Conclusion : Our study confirms the ubiquitous character of predominantly ethnic cancer according to the dominant population. The installation of a pathological laboratory in Toliara would increase the recruitment of cancers.